Implementación de un sistema de almacenamiento de la información, monitoreo y control aplicando el internet de las cosas, para la automatización de un invernadero - Melo Paredes, Nelson Joaquín (2017)
The present project aims at the design, construction and automation of a greenhouse prototype, stored, managed, monitored and controlled through the internet using Google servers and their applications. Introducing an application of IoT (Internet of Things) for crops controlas an alternative to traditional agriculture.With the construction of the prototype of greenhouse it is possible to control different parameters such as temperature, relative humidity and watering, in order to automate, toimprove the quality and quantity of the product. This prototype can be conditioned for any type of crop. The system is controlled remotely and for the administration has an interface made and hosted in the google servers, for monitoring, automatic control and manual is used a web page and an application for devices with android operating system. A wireless communication system is used that sends the information of the greenhouse parameters to the internet, the same that are received, processed and stored by the Google app script and google spreadsheet. Use the Google spreadsheet, web page and android application the sensors are monitored and the actuators are manually and automatically controlled and the greenhouse variables are modified according to the crop.